Gestão democrática no cotidiano escolar : vi-vendo dois lados - Costa, Rosangela Ribeiro da (2007)
This research is focused on the process of democratic management implemented in the educational sphere at Angra dos Reis. One of its major issues investigates in which measure this process contributed to improve the daily actions at schools of that municipality, as well as its implications pedagogical practices, specially those of a teacher that have been to both sides, school and government. First as a teacher of fundamental education d also a member of the discussion forums about the implementaion procedures, and soon after as principle of a multigraded school. This work aims to clarify the process of stablishment of the Act of Democratic Management and its implementation, during the first two administrations of the Partido dos Trabalhadores (Labour Party) 1989-1996, a period of time of quite relevant changes in the educational sphere at Angra dos Reis. The importance of this research relies in reporting a certain type of popular movement, encouraged by actors that occupied the political spheres and that believed in the participation of subjects around the school system.